THE ROLE OF QUALITY COSTS IN IMPROVING PRODUCTS AND ACHIEVING COMPETITIVE ADVANTAGES - M.M. Mohammed Abdul Amir Al – Ghazi; M.M. Abbas Jalil Mohisen (Scholar Express Journals, 2022)
The measurement and presence of quality costs and disclosure in statements and financial reports is an important aspect of economic units because they can make appropriate decisions to improve product quality and development and identify the services provided by products. The research aims to identify quality costs and how they are measured and what their role is to improve product performance and what competitive advantages can be achieved by economic units as a result of their attention and disclosure in financial reports and financial statements. To acquire many competitive advantages, including reduced costs and product quality and increased demand for products, and reflect a positive image on the work of economic unity and the efficiency of its performance and the satisfaction of customers and employees, as well as other competitive advantages that can be achieved. The Iraqi dairy company by identifying how to manage and measure and disclose these costs. The Iraqi dairy company is one of the most important industries to be linked to the lives of future in the future and do not care about quality costs as required and does not disclose them in its financial statements and this makes it difficult for the company to continue In its work and the disappearance of future market share.
Keywords: manage; measure; disappearance; Iraqi